The kingmaker's daughter - Gregory, Philippa. frey50 (New York : Simon & Schuster, 2012)
"Kingmaker" Richard, Earl of Warwick, uses his daughters as political pawns before their strategic marriages place them on opposing sides in a royal war that will cost them everyone they love.
"The Kingmaker's Daughter is the gripping story of the daughters of the man known as the 'Kingmaker,' Richard Neville, Earl of Warwick: the most powerful magnate in fifteenth-century England. Without a son and heir, he uses his daughters Anne and Isabel as pawns in his political games, and they grow up to be influential players in their own right. In this novel, her first sister story since The Other Boleyn Girl, Philippa Gregory explores the lives of two fascinating young women. At the court of Edward IV and his beautiful queen, Elizabeth Woodville, Anne grows from a delightful child to become ever more fearful and desperate when her father makes war on his former friends. Married at age fourteen, she is soon left widowed and fatherless, her mother in sanctuary and her sister married to the enemy. Anne manages her own escape by marrying Richard, Duke of Gloucester, but her choice will set her on a collision course with the overwhelming power of the royal family and will cost the lives of those she loves most in the world, including her precious only son, Prince Edward. Ultimately, the kingmaker's daughter will achieve her father's greatest ambition"--Provided by publisher.
"A Touchstone book."
Keywords: Anne, -- 1456-1485; Sisters -- England; Great Britain -- History -- Edward IV, 1461-1483; Historical fiction